(untitled) (Ameghiniana, 2013)
A fossil chelid turtle from the Montehermosan Land-Mammal Age (Early-Middie Pliocene) of northwestern Córdoba province, Argentina, asigned to the genus Platemus Vagler, is described. Its ocurrence is outside of the present range of living species of the genus Platemus. The specimen is compared with the extant species of this genus. During the Montehermosan Land-mammal Age the Punilla Valley may have been under similar ambiental conditions to those found now a days in alluvial plains of the Paraguay-Paraná systems.